Analysis of maxixe development and productivity as a function of different types of organic fertilizers (Research, Society and Development, 2022)
The gherkin is a vegetable that belongs to the Cucurbitaceae family, widely consumed in the North and Northeast of the country and over the years has been cultivated by family farmers in a traditional way in the undergrowth, which induces the commercial depreciation of the fruits due to contact with the soil. The objective of this work was to evaluate the growth, development and productivity of gherkin as a function of different types of organic fertilizers. The project was carried out at the Agroalimentary Technological Pole of Arapiraca, between March and May 2021. A completely randomized experimental design was used, containing four treatments and five replications, with four forms of manure being studied in the plots, establishing the treatments: without manure, poultry manure, cattle manure and goat manure. The physical characteristics related to the fruit dimensions determined in the study were: total number of fruits, fruit length, fruit diameter and fruit circumference. The total fruit mass, pulp mass and peel mass were evaluated. The gherkin fruit presented the highest averages in the poultry litter treatment, the analysis of variance revealed that the variables total number and circumference of the fruits were significantly expressive when compared to the other fertilizations. Thus, the gherkin fruits showed an excellent development using poultry manure, presenting a superior average of 88.1% of production, when compared to the control.